2013
DOI: 10.1371/journal.pone.0060237
|View full text |Cite
|
Sign up to set email alerts
|

Association of L-Ficolin Levels and FCN2 Genotypes with Chronic Chagas Disease

Abstract: BackgroundL-ficolin (encoded by FCN2) binds to acetylated sugar moieties of many pathogens, including Trypanosoma cruzi, promoting their phagocytosis and lysis by the complement system.MethodsWe investigated L-ficolin levels in 160 T. cruzi infected patients with chronic Chagas disease and 71 healthy individuals, and FCN2 polymorphisms (−986 G>A, −602 G>A, and −4 A>G in the promoter and A258S in exon 8) in 243 patients, being 88 indeterminate (asymptomatic), 96 with cardiac, 23 with digestive and 33 with cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 40 publications
0
39
0
1
Order By: Relevance
“…Polymorphisms in the MBL2 gene with subsequent low levels of MBL increase the risk for Chagas disease, hence confirming that the lectin pathway has a protective role (Weitzel et al, 2012). Lower levels of plasma ficolin-2 have been observed in patients with Chagas disease than in controls (Luz et al, 2013). The T cruzi parasites may induce microvesicles from blood cells, and these microvesicles form a complex on the T cruzi surface with the C3 convertase, the crucial common complement activation step, protecting the T cruzi from complement attack (Cestari et al, 2012).…”
Section: Chagas Disease and The Complement Systemmentioning
confidence: 86%
“…Polymorphisms in the MBL2 gene with subsequent low levels of MBL increase the risk for Chagas disease, hence confirming that the lectin pathway has a protective role (Weitzel et al, 2012). Lower levels of plasma ficolin-2 have been observed in patients with Chagas disease than in controls (Luz et al, 2013). The T cruzi parasites may induce microvesicles from blood cells, and these microvesicles form a complex on the T cruzi surface with the C3 convertase, the crucial common complement activation step, protecting the T cruzi from complement attack (Cestari et al, 2012).…”
Section: Chagas Disease and The Complement Systemmentioning
confidence: 86%
“…In addition, three non-synonymous [18]. Lectin complement proteins have been associated with many infectious diseases including intra and extracellular infections [22][23][24][25]. Our earlier study has shown that, another analogous lectin complement protein ficolin-2 was associated with occurrence of VL [26].…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…Other components of the lectin pathway were also shown to be associated with susceptibility to CD and disease outcome. Lower L‐ficolin levels, correlated to 258S variant, were associated with CD susceptibility and severity of the disease [14]. Furthermore, MASP2 ∗ CD genotypes resulting in low MASP‐2 levels were related to increased risk of chagasic cardiomyopathy.…”
Section: Introductionmentioning
confidence: 95%